Computational biology and genome informatics - Wang, Jason T. L.; Wu, Cathy H.; Wang, Paul P. (World Scientific, 2003)
This study contains articles written by experts on a wide range of topics that are associated with the analysis and management of biological information at the molecular level. It contains chapters on RNA and protein structure analysis, DNA computing, sequence mapping, genome comparison, gene expression data mining, metabolic network modelling, and phyloinformatics. The important work of some representative researchers in bioinformatics is brought together. The topic is treated in depth and is related to, where applicable, other emerging technologies such as data mining and visualization. The goal of the work is to introduce readers to the principle techniques of bioinformatics in the hope that they will build on them to make new discoveries of their own.